DEVELOPMENT AND EVALUATION OF 'EVOLUA SAÚDE': AN APPLICATION FOR THE PROMOTION OF HEALTHY HABITS AND WEIGHT CONTROL IN THE BRAZILIAN CONTEXT (Interdisciplinary Studies Journal, 2024)
Obesity has almost tripled worldwide between 1975 and 2016, with Brazil's obese population doubling over the past 17 years, largely due to sedentary lifestyles and increased consumption of high-calorie, ultra-processed foods. In response, the Evolua Saúde application was developed to assist overweight Brazilian adults, offering guidance on suitable foods and promoting regular exercise. Based on data from Brazil's Ministry of Health and the Compendium of Physical Activities, the application was built using the Flutter framework and follows robust Software Engineering principles. The app was assessed using the Mobile Application Rating Scale (MARS) by nutritionists and physical educators, demonstrating high potential to facilitate healthier habits.
Keywords: mobile app; obesity; flutter; healthy; eating; physical activity